Nai Talim Today: Gandhi's Critique of Industrialism and An Education for Swaraj. (January 2022) - Patil, Pallavi Varma; Sinha, Sujit
The children of today inhabit the planet when CO2 levels have exceeded 400 parts per million (ppm). Crucial planetary boundaries are breached, and the climate crisis has manifested itself menacingly along with several accompanying civilizational crises be it health, socio-economic, political or humanitarian. It is, according to us, the crisis of Industrialism. At this crucial juncture of converging planet-scale disasters where the very survival of humanity is at severe risk, we explore fresh insights into alternative imaginations that can foster a new world where we not just survive but flourish. One such alternative imagination of a good society is that by Gandhi. A century ago, he outlined this vision as Swaraj and, over the years, fleshed out this vision. It is for this Swaraj that in 1937, Gandhi, conceptualizing his educational ideas, initiated a programme known as Nai Talim. Swaraj was diametrically opposite to Industrialism. And, therefore, Nai Talim was in sharp contrast to the state-approved school education that promoted Industrialism. In this article, we give a brief outline of Swaraj; highlight the interconnections between Swaraj and Nai Talim; and expand on ways in which one can reimagine Gandhi's Nai Talim for contemporary times. We also argue that such an imagination of reinvented Nai Talim is possible today in Indigenous communities, where there is a spirited resistance to industrialism. And as an example, we look at the ongoing experiment of the Zapatistas of Chiapas, Mexico.